Bringing the home into school: learning and connecting through mathematics education during the time of a pandemic - Hunter J; Hunter R; Tupouniua J; Leach G (Springer Nature B.V, 2022)
The COVID-19 pandemic brought with it a new way of being in a changed and uncertain world. Aotearoa/New Zealand took a well-being approach and in turn, we share the positive outcomes which resulted for some low socio-economic schools and communities in relation to teacher learning and relationships with families. In this article, we report on how teachers and schools connected with diverse students and their families during the period of remote learning. We draw on the responses from 20 teachers and school leaders who participated in interviews. Following the wider government focus, schools took a well-being first approach which led to increased connections and positive home/school relationships. The results highlight how a disruptive event such as COVID-19 can also be a time to focus on strengths of diverse communities and gain insights. We demonstrate that while focusing on mathematics, teachers and school leaders gained insights related to their students’ funds of knowledge and saw opportunities for learning for students, parents, and the teachers themselves.
Keywords: Culturally sustaining mathematics pedagogy; Equity; Home-school partnerships; Primary education; Teacher learning